2015
DOI: 10.1038/srep08762
|View full text |Cite
|
Sign up to set email alerts
|

X-ray phase contrast tomography by tracking near field speckle

Abstract: X-ray imaging techniques that capture variations in the x-ray phase can yield higher contrast images with lower x-ray dose than is possible with conventional absorption radiography. However, the extraction of phase information is often more difficult than the extraction of absorption information and requires a more sophisticated experimental arrangement. We here report a method for three-dimensional (3D) X-ray phase contrast computed tomography (CT) which gives quantitative volumetric information on the real p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 32 publications
0
42
0
Order By: Relevance
“…In a first report, the phase and transmission tomograms of a human artery obtained with the single-shot XST mode (see Section 3.1) were shown [89]. The superior sensitivity to density differences of the phase signal over the transmission signal, here between the artery lumen and walls, was observed in a qualitative way; see Figure 10I in Section 7.2.…”
Section: Speckle-based X-ray Phase-contrast and Dark-field Tomographymentioning
confidence: 99%
See 3 more Smart Citations
“…In a first report, the phase and transmission tomograms of a human artery obtained with the single-shot XST mode (see Section 3.1) were shown [89]. The superior sensitivity to density differences of the phase signal over the transmission signal, here between the artery lumen and walls, was observed in a qualitative way; see Figure 10I in Section 7.2.…”
Section: Speckle-based X-ray Phase-contrast and Dark-field Tomographymentioning
confidence: 99%
“…It has been demonstrated that microfocus laboratory sources provide sufficient spatial coherence for successful implementation of X-ray speckle-based imaging [85]. Alternatively, it has been proposed to use a random pattern created by absorption rather than interference effects to track the beam wavefront under conditions of low spatial coherence [89,136]; see Section 5.…”
Section: Practical Experimental Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the several techniques developed in the last years, a method based on tracking of near-field speckles has several advantages [4][5][6][7][8]. The setup, data acquisition and analysis procedures are relatively simple, it provides multicontrast signals in different directions, and it works well not only at synchrotron facilities, but also at polychromatic laboratory sources [9,10].…”
Section: Introductionmentioning
confidence: 99%